Mathematical Methods of Surface Roughness Evaluation of Areas with a Distinctive Inclination - Bilek, Ondrej; Pata, Vladimir; Kubisova, Milena; Reznicek, Martin (Manufacturing Technology Journal, 2018)
Surface roughness is one of the most significant evaluation factor in metal machining operations. Despite the small descriptiveness is usually quantified as the arithmetical mean roughness Ra especially in the automotive industry. In order to maintain the desired surface roughness, the appropriate setting of machining parameters is important to be set before the actual cutting process. The objective of this research is to analyse the effect of machining parameters on surface roughness of stainless steel X153CrMoV12-1 in CNC milling of slope surfaces with sintered carbide tool. The data were processed using multiparametric statistical methods to find optimal results. Linear regression models and probability dendrograms of similarities were determined for cutting conditions, cutting tools and slope of machined surfaces.
Keywords: CNC Milling; Cutting Tool; Multiparametric Statistical Methods; Surface Roughness; Surface Slope